2011
DOI: 10.1007/s10916-011-9742-x
|View full text |Cite
|
Sign up to set email alerts
|

Decision Support Algorithm for Diagnosis of ADHD Using Electroencephalograms

Abstract: Attention deficit hyperactivity disorder is a complex brain disorder which is usually difficult to diagnose. As a result many literature reports about the increasing rate of misdiagnosis of ADHD disorder with other types of brain disorder. There is also a risk of normal children to be associated with ADHD if practical diagnostic criteria are not supported. To this end we propose a decision support system in diagnosing of ADHD disorder through brain electroencephalographic signals. Subjects of 10 children parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 21 publications
0
45
0
Order By: Relevance
“…High rates of classification accuracy for both the original sample (91 %) and a subsequent validation sample (94 %) were obtained [41]. This, and other studies, using a semi-supervised feature selection to define new features of the EEG signal [42], as well as studies using graph theory and community pattern analysis of EEG-derived functional connectivity [43] may provide new avenues to identify and test EEG measures, which can both tolerate sample heterogeneity and provide maximal discrimination between individuals with and without ADHD.…”
Section: New Methods For Adhd Discriminationmentioning
confidence: 58%
“…High rates of classification accuracy for both the original sample (91 %) and a subsequent validation sample (94 %) were obtained [41]. This, and other studies, using a semi-supervised feature selection to define new features of the EEG signal [42], as well as studies using graph theory and community pattern analysis of EEG-derived functional connectivity [43] may provide new avenues to identify and test EEG measures, which can both tolerate sample heterogeneity and provide maximal discrimination between individuals with and without ADHD.…”
Section: New Methods For Adhd Discriminationmentioning
confidence: 58%
“…Similarly, Abibullaev and An [36] obtained a maximal accuracy of 97%, using relative theta measures recorded from nine frontal scalp electrodes. Based on these accuracy rates, we may conclude that the potential of multivariate machine learning tools in EEG-based diagnostics is intriguing but, as such studies remain sparse and the results offer no simple interpretation (also c.f.…”
Section: Neurophysiological Candidates For Biomarkers Of Adhdmentioning
confidence: 99%
“…In many ways this is a refinement from previous work that looked at specific EEG bands. Neurophysiological studies have previously shown that children with ADHD exhibit specific patterns on the electroencephalogram (EEG) and this has been utilized clinically to diagnose, treat and even predict response to treatment with medication [14], [15], [16], [17], [18]. EEG studies of children with ADHD showed the majority to exhibit abnormal patterns of resting cortical activity including increased slow-wave activity (primarily theta waves), decreased fast-wave activity (primarily beta waves) and increased beta-theta ratio [19], [20], [21].…”
Section: Discussionmentioning
confidence: 99%